Towards a theology of subjectivity from Scholasticism to the life of God - Yangali Núñez, Oscar Edmundo (2017)
In this essay, I aim to interpret Miles's book "God. A biography" based on certain notions of scholastic thought, especially Suarezian, in order to adapt this theology to the demands of subjectivity. First, I examine the concept of God derived from the scholastic tradition and how -although it constitutes an important inheritance- it is not sufficient for the understanding of the Christian God. Second, I expose the theses of Miles and those of the scholastic tradition concerning the creation of the human being in the image and likeness of God and the individuality of both. Finally, I explain how these postulates can be reconciled through a theology of subjectivity in order to reestablish a dialectical relationship between human beings and God.